Oral tolerance induced by OVA intake ameliorates TNBS-induced colitis in Mice - Paiatto, Lisiery N. [UNESP]; Silva, Fernanda G. D.; Bier, Julia; Brochetto-Braga, Márcia R. [UNESP]; Yamada, Áureo T.; Tamashiro, Wirla M. S. C.; Simioni, Patricia U. [UNESP] (Public Library of Science (PLoS), 2017)
Introduction Literature data have shown that the consumption of dietary proteins may cause modulatory effects on the host immune system, process denominated oral tolerance by bystander suppression. It has been shown that the bystander suppression induced by dietary proteins can improve inflammatory diseases such as experimental arthritis. Here, we evaluated the effects of oral tolerance induced by ingestion of ovalbumin (OVA) on TNBS-induced colitis in mice, an experimental model for human Crohn's disease. Methods and Results Colitis was induced in BALB/c mice by instilling a single dose of TNBS (100 mg/kg) in ethanol into the colon. Tolerized mice received OVA (4mg/mL) dissolved in the drinking water for seven consecutive days, prior to or concomitantly with the intrarectal instillation. Control groups received protein-free water and ethanol by intrarectal route. We observed that either the prior or concomitant induction of oral tolerance were able to reduce the severity of colitis as noted by recovery of body weight gain, improvement of clinical signs and reduction of histological abnormalities. The in vitro proliferation of spleen cells from tolerant colitic mice was lower than that of control mice, the same as the frequencies of CD4+ T cells secreting IL-17 and IFN-ã. The frequencies of regulatory T cells and T cells secreting IL-10 have increased significantly in mice orally treated with OVA. The levels of inflammatory cytokines (IL-17A, TNF-α, IL-6 and IFN-ã) were lower in supernatants of cells from tolerant colitic mice, whereas IL-10 levels were higher. Conclusion Our data show that the modulation of immune response induced by oral tolerance reduces the severity of experimental colitis. Such modulation may be partially attributed to the increase of Treg cells and reduction of pro-inflammatory cytokines in peripheral lymphoid organs of tolerant mice by bystander suppression.